Changing addictive behavior : bridging clinical and public health strategies - Tucker, Jalie Ann (Guilford Press, 1999)
This volume proposes that prevailing clinical approaches to treating addictive behaviors are actually best suited to a minority of the population with problems--in the case of substance abusers, those with substantial functional impairment and physical dependence. But what about persons with mild to moderate addictive behavior problems, for whom intensive treatment may prove unnecessarily costly, disruptive, and stigmatizing? Contributors draw upon cutting-edge theory and research to examine ways that traditional therapeutic treatments can be supplemented by public health interventions that extend the reach and effectiveness of care. The book points the way toward necessary evolutions in the roles of behavior change specialists in today's challenging health care environment.